A‐site Cation Engineering for Highly Efficient MAPbI3 Single‐Crystal X‐ray Detector. Issue 49 (23rd October 2019) - Huang, Yanmin; Qiao, Lu; Jiang, Yuanzhi; He, Tingwei; Long, Run; Yang, Fan; Wang, Lin; Lei, Xiaojuan; Yuan, Mingjian; Chen, Jun
Abstract: Metal halide perovskites have emerged as a new generation of X‐ray detector materials. However, large‐sized MAPbI3 single crystals (SCs) still exhibit lower performance than MAPbBr3 SCs in X‐ray detection. DFT (density functional theory) simulations suggest the problem could be overcome by alloying large‐sized cations at the A site. The alloyed process could notably decrease the electron–phonon coupling strength and increase the material defect formation energy. Accordingly, centimeter‐sized alloyed DMAMAPbI3 (DMA=dimethylammonium) and GAMAPbI3 (GA=guanidinium) SCs are obtained. Electrical characterizations confirm the GAMAPbI3 SCs display improved charge collection efficiency. It also exhibits a remarkable reduction of dark current, an important figure of merit for X‐ray detectors. With a judiciously designed device architecture, the overall detector performance confirms GAMAPbI3 SCs as one of the most sensitive perovskite X‐ray detectors to date. Abstract : Detective work : DFT simulations and experimental results suggest that an alloyed large cation at the "A‐site" can improve the performance of MAPbI3 (MA=CH3 NH3 ) single‐crystal (SCs) based X‐ray detectors. Thus, alloyed GAMAPbI3 SCs (GA=guanidinium) are prepared and found to be one of the best‐performing perovskite X‐ray detectors.